How symbolic human resource function actions affect the implementation of high‐performance work practices: The mediating effect of influence on strategic decision‐making - Hermans, Michel; Ulrich, Michael D. (Human resource management journal, 2021)
ABSTRACT Despite growing evidence of human resource management (HRM)‐performance linkages, the department entrusted to implement high‐performance work practices (HPWP), the human resource (HR) function, is perceived to lack organisational power. Drawing on political perspectives on organisational behaviour, we argue that the HR function can increase its influence on strategic decision‐making in the organisation by developing symbolic HR function actions such as interacting effectively with directors, involving line managers in HRM, outsourcing and using HR metrics. Next, we explore how HR function influence is associated with implementation of HPWP. Finally, we test whether the mediation mechanism is moderated by industry type within a global sample of 11,780 raters at 409 business units. The findings of this study have important implications for HR professionals who seek to implement HPWP in their organisations. It provides insight into how HR functions can develop and use influence towards increasing line managers' willingness to implement such practices.